The theoretical foundation to application universal index of somatic health of students during the lesson of physical education - Kopa V.M (Kharkov National Pedagogical University, 2012)
In this article has been considered and grounded the region of application of universal index physical health (UIPhH) between students auditory. In experiment has been taken 153 student's another level of health from 16 to 25 years. Has been proposed two formulas - for students-sportsmen's and students with chronicle diseases. Has been correlated same indexes: UIPhH, Skibinskaya's index, index of Letunov, Rufe's index and another. Has been proved, that theses indexes correlated and had identical physiological composition. Has been proved, that application UIPhH be required individually - for students-sportsmen's and students with chronicle diseases. Has been estimate, then the students with chronicle diseases of heart system with symbatotonic reaction has been better reaction on physical load then the students with vagotonic reaction (on the rate "satisfactory"). Also, the manes have been better the level correlation between indexes than woman. Practically has been proved, than for simply calculate take a sense take only UIPhH.